Graphic Organizers Support Young L2 Writers’ Argumentative Skills (GIST – Education and Learning Research Journal, 2018)
Learners are increasingly required to analyze critically information presented in languages other than their first to form reasoned opinions and solve problems. It is thus urgent to develop their argumentation skills, needed not only for academic success but also later professional life—and, indeed, by participant citizens in democratic societies. Although there has been some increased interest in teaching argumentation at pre-tertiary levels, this remains a relatively unexplored issue in Colombia (and, indeed, much of the developing world), certainly when considering writing in a second language. This qualitative study analyzed the influence of graphic organizers on the development of argumentative written tasks by a group of sixth-grade English learners. Data was collected through surveys, questionnaires, focus group, a teachers’ journal, and students’ written artifacts and analyzed through the grounded theory approach. Findings revealed that using graphic organizers positively influenced learners’ argumentative writing skills, specifically through supporting strategic information planning and argumentative linearization during the pre- and while-writing stages. These understandings show that younger learners can develop complex argumentative writing skills in a second language, thereby offering significant lessons for teachers of language—and content—in both the first and additional languages.
Keywords: Writing; argumentation; graphic organizers; additional language; problem-based tasks